DEVELOPING SYSTEMATIC DESIGN OF INSTRUCTION USING TRADITIONAL GAMES INTO SPEAKING GAME AS AN INOVATION OF SUPPORTING ENGLISH TEACHING MATERIAL - afita dewi prastiwi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
Abstract:Speaking English was a problem for Junior High School students. Improving students’ speaking ability was a difficult thing for the teacher and integrating speaking with character education as stated in curriculum was an additional work for the teacher.This study was conducted to develop traditional games into speaking games as an inovation of supporting English teaching material which was integrated with character education in Junior High School. Research and Development design in developing the games was used to achieve the aim of the study. The sources of the data were the students and teachers’ need analysis and the teacher and students’ responses toward the games. The data was analyzed descriptively in terms of proposed teacher’s guideline for teaching speaking using traditional games integrated with character education. The development process of the product in this study was successful to motivate the students to speak and to build the students’ character.